DIAGNOSE THE GAP BETWEEN THE ACTUAL REALITY OF THE COMPANY AND THE REQUIREMENTS OF THE ENERGY MANAGEMENT SYSTEM OF THE STANDARD WITH THE REQUIREMENTS OF STANDARD ISO 50001: 2018 - Tabarak Sami Ahmed; Assist. Dr. Qabas zouhair Abdel Karim; Assist. Dr. Ali Abdul Karim Al-Saffar (Scholars Digest Publishing, 2024)
Objective: The research aims to determine the extent of the possibility of applying the provisions of ISO 50001:2018, which are (leadership, planning, support, operation) in the General Company for Electric Power Production in the Central Region. Methodology: The research starts from the problem of determining the size of the gap between the actual reality and the requirements of the provisions of leadership, planning, support and operation of The Standard ISO 50001:2018, and the high energy consumption and the resulting high costs that fall on the company, in addition to the company’s lack of knowledge of the importance of applying Specification 50001. ISO 2018: What benefits the employees and the company and what it gains in terms of competitive advantages and value. The study methodology was based on a case study represented by observation, personal interviews, and the use of a checklist for comprehensive and realistic analysis and access to scientific facts. Results: In light of the conclusions, a large gap appeared between the actual reality of the General Company for Electric Power Production in the Central Region and the requirements of the energy management system Of The Standard the specification (ISO 50001:2018), as the size of the gap in the leadership item reached (55%), while the size of the gap in the planning item reached (76.5%), as for the support item, the size of the gap is estimated at (59.25%), and finally the size of the gap for the operation item reached (71.75%). Added value: A number of recommendations were proposed, in addition to formulating work procedures and a guide to help the company implement the energy management system in accordance with ISO 50001:2018
Keywords: Energy Management, Energy Management System, Standard (ISO 50001: 2018).